Smooth particle hydrodynamics modelling of liquid-sediment system and coastal wave breaker - Ng F.C.; Zawawi M.H.; Azman A.; Abas A.; Razak N.A.; Aziz N.A.; Zahari N.M. (Springer Science and Business Media Deutschland GmbH, 2023)
Beaches; Erosion; Froude number; Liquids; Sedimentation; Velocity measurement; Water waves; Beach profile; Beach profile erosion; Iribarren numbers; Numerical scheme; Scouring; Smooth particle hydrodynamics; Smoothed particle hydrodynamic; Smoothed particle hydrodynamics; Wave breaker; Wave frequencies; Sediment transport; beach erosion; beach profile; coastal water; Froude number; hydrodynamics; hydrological modeling; wave breaking